(3QSGdI aj GdHSedIs - (3ESeGYjd Hf Zfje GdLhgQj,J (B1165 (3g` s
(3ChdgG (B:s
(3MeOkG deG fM GdHjGf haGJM GHhGH GdJHjGf hHYO ajbhd bO hVYJ aejG eVi QSGdI JJVef eG ETJedJ Ydjg GdHSedI ef GdeGMK GdTQjaI hJMJhi Ydi eGajgG ef GdahGFO GdYRjRg s
(3BNQgG (B:s
(3aCQGO Gf jchf GSeg hbGjI dCSeg JYGdi hbGfG Gddg ef cjOGdMGSOjf hYUefG ef TQ GdeJYUHjf GdeYJOjf HLGg GTQa GdeQSdjf hBdg hUMHg GLeYjf hGdMeO ddg hcai hSdGe Ydi YHGOg GdPjf GUWai hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B285s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdGScfOQjI s
Keywords: (3GdadSaI hGdefWbs